Characterization and oxygen saturation study of human retinal blood vessels evaluated by spectroscopic Optical Coherence Tomography Angiography. (February 2020) - Poddar, Raju; Basu, Mainak
Highlights: A FDML powered OCT system is demonstrated for imaging of human retina. A new PCA based spectroscopic OCT and angiography is reported. The method is utilized for measurement of O2 saturation status in retinal vessels. The method is testified for effective blind source data extraction from OCT image. The PCA method with a scanning STFT produces relative O2 saturation in retina. Abstract: Optical coherence tomography is non-invasive diagnostic technique for performing high resolution (~µm) cross sectional imaging. In this article, we demonstrate characterization and oxygen saturation studies of human retinal blood vessels with Principal Component Analysis (PCA) based Spectroscopic Optical Coherence Tomography-based Angiography. A Fourier Domain Mode-Locked laser having an axial imaging resolution of ~7.5 µm, with an A-scan sweep rate of 1.7 MHz and centre wavelength of 1060 nm, was utilized as an OCT source. PCA has been used in conjunction with a scanning Short Time Fourier Transform, procedure to isolate the probable amount of oxygenated and deoxygenated haemoglobin and extract the information from individual OCT frames, without any external fitting model. This technique could provide useful insight into an effective blind source data extraction technique for medical image analysis. The technique proposed in this article, has a significant advantage in requiring no additional filtering or noise reduction technique in order to accurately extract the required information. It can also be used for ophthalmological research to determine the oxygen saturation of human retinal blood circulation, which may be helpful for identification of abnormalities related to human eye.